The Influence of Parenting and Peers on Early Childhood Character (Journal of Primary Education, 2020)
Character is very important to build from an early age because it affects how individuals perceive themselves and their environment in everyday life. This study aims to explore the influence of parenting and peers on early childhood character. It is a quantitative correlational research employing a survey approach. The samples of this study were 169 early childhoods of Raudhatul Athfal Ambawara who had obtained permission from their parents. The data of parenting variables were collected by using questionnaires, while the data of peers and character variables were obtained through observation. The data analysis technique used was multiple regression analysis with the help of SPSS 20.0 software. The results show that there is an influence of parenting on early childhood character with a t value of 11,744 and a sig. value of 0.00. This study also found that peers have an influence on early childhood character with a t-value of 9,090 and a sig. value of 0.00. Implementing a proper parenting to early childhood and fostering social attitudes to interact with their peers are necessary to build their character.